Use of nasogastric tube in emergency situation to prevent LMA ProSeal down folding: a simple method - Tiwari, Tanmay; Kannaujia, Ashish (International Journal of Research in Medical Sciences, 2017)
Securing of airway and prevention of aspiration are of utmost importance during airway management in the field of anesthesia and emergency medicine. Now a days laryngeal mask airways are being very frequently used for securing airway in elective as well as emergency conditions. LMA-ProSeal™ (PLMA) (Laryngeal Mask Company, Henley-on-Thames, UK) has an added advantage over classical LMA (CLMA) as it has gastric port for insertion of Ryle’s tube which allows suctioning of gastric contents. PLMA also allows ventilation with higher pressures so it is preferred over CLMA, The design of the PLMA reliably allows positive pressure ventilation up to 30–40 cm H2O pressure. Use of PLMA is not always a smooth ride and may offer certain difficulties.